Mobile IoT Cloud-based Health Monitoring Dashboard Application for the Elderly - Kadir A.D.I.A.; Alias M.R.N.M.; Dzaki D.R.M.; Azizan A.; Din N.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Data visualization; Life cycle; mHealth; Monitoring; Average life; Cloud-based; Dashboard; Elderly health monitoring; Elderly people; Global health; Health monitoring; Health services; Life expectancies; Mobile IoT; Internet of things